2021
DOI: 10.1002/cpdd.923
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis Clearance of Enarodustat (JTZ‐951), an Oral Erythropoiesis Stimulating Agent, in Patients with End‐Stage Renal Disease

Abstract: The dialysis clearance of enarodustat (JTZ‐951) was determined in patients (N = 6) with end‐stage renal disease on hemodialysis. Enarodustat (5 mg PO) was administered before (day 1) and after hemodialysis (day 8) with pharmacokinetic assessments on the 2 occasions. Dialysis clearance was based on plasma and dialysate enarodustat concentrations. Fraction of administered dose recovered in dialysate, total predialyzer and postdialyzer plasma enarodustat concentrations, and total and unbound venous plasma concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…The population estimates of CL/F from the final PK model (0.892 L/h) was in agreement with the value (0.820 L/h) calculated from noncompartmental analysis with intensive PK data in Japanese patients with HDD‐CKD 32 . The population estimates of V/F was 10.9 L. Enarodustat had high plasma protein binding (>99%) in patients with end‐stage renal disease 33 and was not substrate of the hepatic uptake transporters such as organic anion transporting polypeptides 1B1 (OATP1B1) and OATP1B3 in vitro. Considering these PK characteristics, the distribution volume of enarodustat was considered relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…The population estimates of CL/F from the final PK model (0.892 L/h) was in agreement with the value (0.820 L/h) calculated from noncompartmental analysis with intensive PK data in Japanese patients with HDD‐CKD 32 . The population estimates of V/F was 10.9 L. Enarodustat had high plasma protein binding (>99%) in patients with end‐stage renal disease 33 and was not substrate of the hepatic uptake transporters such as organic anion transporting polypeptides 1B1 (OATP1B1) and OATP1B3 in vitro. Considering these PK characteristics, the distribution volume of enarodustat was considered relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…30 Following the administration of 5 mg enarodustat to hemodialysis patients, more than 99% of enarodustat in plasma is mainly bound to albumin. 31 The percent distribution of enarodustat to human blood cells (in vitro) was 2.5%-6.8%. In vitro studies with hepatic microsomes and cytochrome P450 (CYP) isoenzymes showed that enarodustat was slightly metabolized, mainly by CYP2C8 and CYP2C9 with minor involvement of CYP3A4.…”
Section: Pharmacokineticsmentioning
confidence: 97%
“…Therefore, enarodustat can be administered regardless of the dialysis schedule, and dose supplementation is not required for hemodialysis patients. 31…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 2 more Smart Citations